PSIKOLOGI HUMANISTIKDALAM PERILAKU BIBLIOMANIA DI KALANGAN MAHASISWAILMU PERPUSTAKAAN UIN SUNAN KALIJAGAYOGYAKARTA - Masruri, Anis; Maulidina, Fina (Universitas Islam Negeri Raden Intan Lampung, 2019)
This research is a qualitative descriptive study, an analysis of the humanistic psychology of bibliomania behavior experienced by students of the UIN Sunan Kalijaga Library Science. The condition where a person has an obsessive-compulsive form of excessive desire to collect books continuously. The goal of the research is to know someone's psychological desire to buy a book and feel relieved in collecting books even though not read. the main motivation in gathering lots of books is just to add to his own insight but when someone has a love and passion for reading books, then all desires related to books will be an extraordinary intellectual adventure. So it is not surprising when a person can be infected with biblicism if he has an excessive desire to buy, read, save, and enjoy books. It's better to love books and buy books naturally, if there is still a large collection of books stored and unread, then hold to buy more books. after reading a book it would be nice to give a review or some kind of ability to write from the results of reading a book. From this creative attitude, we can develop the skills and potential we have to build a civilized nation.